2021
DOI: 10.1016/j.jinorgbio.2020.111330
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of half-sandwich (η5-Cp*)Rh(III) cation with histidine containing peptides and their ternary species with (N,N) bidentate ligands

Abstract: Our goal was to explore the possible interactions of the potential metallodrug (η 5 -Cp*)Rh(III) complexes with histidine containing biomolecules (peptides/proteins) in order to understand the most important thermodynamic factors influencing the biospeciation and biotransformation of (η 5 -Cp*)Rh(III) complexes. To this end, here we report systematic solution thermodynamic and solution structural study on the interaction of (η 5 -Cp*)Rh(III) cation with histidine containing peptides and their constituents ((N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 66 publications
(136 reference statements)
0
9
0
Order By: Relevance
“…It was reported that half-sandwich RuCym and RhCp* complexes mostly preferred to bind to the His-imidazole residue of the protein. 54–58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that half-sandwich RuCym and RhCp* complexes mostly preferred to bind to the His-imidazole residue of the protein. 54–58…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that half-sandwich RuCym and RhCp* complexes mostly preferred to bind to the His-imidazole residue of the protein. [54][55][56][57][58] At first, UV-vis spectral changes of the complexes were followed over time in the presence of 10 equiv. MIM (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…(The corresponding stability constants and protonation constants were taken from refs. [53], [92] and [93], except for the (O,O) chelated species at 0.20 M KCl, which were determined in this work and are as follows: [ML] + = 7.08; [MH −1 L]= −1.12). As Figure 4 reveals, in the strongly acidic pH-range (1-3) the stability of the (N,N) 5 chelate is comparable with that of the (O,O) chelate, but upon increasing the pH, the latter becomes the most stable in the whole pH-range.…”
Section: Speciesmentioning
confidence: 98%
“…The constants in square brackets are only indicative values, since the systems were non-equilibrated. (taken from [151] Since Rh(III) is diamagnetic (low spin d 6 cation) in all our complexes, NMR is a straightforward method to gain information on the solution structure and also to support the solution speciation. Indeed, all L 5(m) complexes have slow ligand exchange on the NMR timescale, and thus the changes in speciation can be easily followed (Fig.…”
Section: The Interaction Of Half-sandwich (η 5 -Cp*)rh(iii) Cation Wi...mentioning
confidence: 99%
“…4.27A). Considering the difference between the two ligands, the most plausible reason of isomer formation is the metal-promoted deprotonation and coordination of imidazole N 1 H group of L 5 , and the subsequent formation of different oligomers [151]) via imidazolato bridges. This would not be very unusual, since the crystal structure of an imidazolato-bridged (η 5 -Cp*)Rh(III) complex has been already reported in the literature [159].…”
Section: The Interaction Of Half-sandwich (η 5 -Cp*)rh(iii) Cation Wi...mentioning
confidence: 99%